An optimization model of make or buy decision and quality improvement of components using rebate. Issue 1 (1st January 2020) - Rosyidi, Cucuk Nur; Imamah, Namrotul Uela Fatakunul; Jauhari, Wakhid Ahmad
Abstract: The aim of this research is to develop a make or buy decisions optimization model involving rebate for quality improvement to minimize a total cost comprising of manufacturing cost, quality loss, and lateness cost by taking into consideration the process capability, production capacity, supplier capacity, costumer demand, due date, and process routing. Several constraints are imposed in the model include tolerance limits, process variance of the components, minimum number of the selected machine or supplier, and the quality level before and after rebate. A numerical example is given to show the application of the model. The optimization results show that the inclusion of the rebate to the model gives benefits to the system by improving the quality and reducing the quality loss. From the analysis, prevention cost has the most significant impact on suppliers total cost.